You are on page 1of 7

Laplace Transform

Definition & some Transformation

Theory

Definition of Laplace Transform:


It is defined as,

() dt
0

F(s) = L[f(t)] =

Note: Here we are using small letters for writing the time domain
quantities while capital letters are used for transformed (frequency
domain quantities) quantities.
Eg. i(t) or v(t) is the current or voltage in time domain and I(s) or
V(s) is the current or voltage in Laplace transform(frequency
domain).
Laplace Transform is also defined as a method of transforming
time domain quantities into frequency domain.

Laplace Transform of Important Functions


1. Constant Function k:
Here, f(t) = k
L[k] =

() dt
0

=k
L[k] =

dt

k
s

2. Function :
Here, f(t) =
L[ ] =

() dt =

Put st = x, dt =
L[ ] =


dt
0

dx
s

dx
s
1

Laplace Transform

Definition & some Transformation

=
L[ ] =
L[ ] =

1
+1

dx

+1
+1
!

for n>0

+1

3. Unit Step Function:


It is defined as,
u(t) = 1 t>0
= 0 t<0
The Laplace Transform is given as,

L[u(t)] =
L[u(t)] =

1.

4. Shifted or Delayed Unit-Step Function:


It is defined as,
u(t-a) = 1
t>a
=0
t<a
Laplace Transform of u(t-a) is
L[u(t-a)] =
L[u(t-a)] =

1.

5. Unit-Impulse Function:
It is defined as,
(t) = 0
t0
and

(t)dt

=1

t=0
2

Theory

Laplace Transform

Definition & some Transformation

Laplace Transform is given by,


L[ (t)] =

t est dt

L[ (t)] = 1
6. Unit-Ramp Function:
It is defined as,
r(t) = t
t>0
=0
t<0
Laplace Transform is given as,
st
te dt
0

L[r(t)] =
L[r(t)] =

1
2

7. Delayed Unit-Ramp Function:


It is defined as,
r(t-a) = t t>a
= 0 t<a
Laplace Transform is given as,
L[r(t-a)] =
L[r(t-a)] =

st
te dt

8. Sine Function:
We know that sint =

1
2

Laplace Transform is given as,


1

L[sint] = L
=
L[sint] =

2
1

1
2

1
+

2 + 2

9. Cosine Function:
We know, cost =

1
2

+
3

Theory

Laplace Transform

Definition & some Transformation

Theory

Laplace Transform is given as,


1

L[cost] = L
=

L[cost] =

1
2

1
+

2 + 2

10. Exponential Function :


Here, f(t) =
L[ ] =

at st
e e dt
0

( )

=
L[ ] =

(sa)t
e
dt
0

Properties of Laplace Transform:


A) Linearity:
The transform of a sum of time functions is the sum of the
transforms of the individual functions, that is
L[a1f1(t) + a2f2(t) ] = a1F1(s) + a2F2(s)
Where a1 and a2 are constants.
Proof:
L[a1f1(t) + a2f2(t) ] =

= a1

a1 f1 t + a2 f2 t dt

() dt
0 1

= a1F1(s) + a2F2(s)
B) Time Scaling:
1

If L[f(t)] = F(s) then L[f(at)] =


Proof:
Let x = at then dx = a dt
4

+ a2

() dt
0 2

Laplace Transform

Definition & some Transformation

L[f(at)] =
=

Theory

(/)
()
dt
=
()

0
0

1
(/)
dx
()
0

C) Frequency Shift Theorem:


If L[f(t)] = F(s) then L () = F(s+a)
Proof:
L () =

. dt =

. (+) dt

= F(s+a)
D) Time Shift Theorem:
If L[f(t)] = F(s) then L[f(t-a)] = e-asF(s)
Proof:

L{f(t)} =
L{f(t-a)} =

. dt
. dt

Put t-a = x, dt = dx
When t=a, x=0
t , x
L{f(t-a)} =

. (+) dx = e-as

= e-as

. dx

. dt

= e-asF(s)
E) Initial value theorem:
The initial value of a function f(t) is the value at t = 0
provided f(t) is continuous at t=0.
If it is discontinuous at t=0, the initial value is the limit as
t 0+. The initial value is obtained using
f(0+) = lim0+ () = lim ()
This is called as initial value theorem.
Proof:
5

Laplace Transform

Definition & some Transformation

Theory

From the time differentiation property we have,


L{f(t)} = sF(s) f(0)
sF(s) = L{f(t)} + f(0) =

() + f(0)

lim () = lim

() + f(0)

lim () + f(0)

= 0 + f(0) = f(0)
= lim0 ()
F) Final value Theorem:
It is the value of f(t) as t , given by f() = lim ()
= lim0 (). This is called as Final value theorem.
Proof:
From the time differentiation property
L{f(t)} = sF(s) f(0)
sF(s) = L{f(t)} + f(0) =

() + f(0)

Taking limit as s 0
lim0 0

()

=
()
0
0 0
= ()
0 = f() f(0)

= lim

Since f(0) is independent of s,


lim 0 = f(0-)
0

Thus above equation becomes,


lim sF(s) f(0-) = f() f(0-)
0

i.e. f() = lim sF(s)


0

Laplace Transform

Definition & some Transformation

Theory

G) Time-Differentiation Theorem:
It states that,
If L{f(t)} = F(s) then,
L{f(t)} = sF(s) f(0)
L{f(t)} = s2F(s) sf(0) f(0)
In general,
L{f(t)} = sF(s) sn-1f(0) sn-2f(0) sn-3f(0) - f(n-1)(0)